IMPACT OF DIGITAL PAYMENT SYSTEMS ON CONSUMER BEHAVIOR AND BUSINESS GROWTH IN DODDABALLAPUR, INDIA (International Journal of Food and Nutritional Sciences, 2023)
This study examines the influence of digital payment systems on consumer behavior and business development in Doddaballapur, India. It focuses on the growing use of platforms such as the Unified Payments Interface (UPI), mobile wallets, and digital banking, which have transformed interactions between consumers and businesses. Utilizing data from a survey of 500 consumers and interviews with 20 local business owners, the research identifies the advantages and challenges associated with digital payment adoption. While these systems offer enhanced convenience and speed, issues like security concerns, varying levels of digital literacy, and transaction costs pose barriers to broader acceptance. The paper also investigates how small and medium enterprises (SMEs) in Doddaballapur are leveraging digital payments to expand and optimize their operations.